Stato filosofico nel paziente in trattamento dialitico - Sandro Scipioni; Lucia Giuliani; Valentina Micheluzzi; Francesco Burrai (AboutScience Srl, 2020)
The following study is original respect to the scientific panorama in fact, through a literature review that uses a qualitative metasynthesis method and follows the aggregative or meta-aggregative approach of the Joanna Briggs Institute, it returns to the reader 3 main results: the Anguish for an imminent death, the relationship with the body, sexuality, pain and dimension of the person, and the Perception of time and existentialism. Reflecting on the "philosophical state or philosophy of the patient in dialysis treatment" through these 3 macro-themes means investigating in depth the words of the patients, extrapolating their feelings, fears and worries, so as to understand their overall view of life and illness even in the most veiled aspects. Finally, the reflection will be used to direct the care of professionals towards a real and meaningful appointment of the dialysis patient. All thanks to the philosophy that goes beyond the methodology of research and evaluation of data, through the interpretation, direction and demonstration of the concept of limit, as an intrinsic part of man, disease and science. (Humanization)